Neglect of people with disability by the African church - Maake J. Masango (HTS Teologiese Studies/Theological Studies, 2019)
The African community, as well as the church, has always cared for people with disability. The main problem they faced is that they care for them by imposing their own agenda on them. In other words, they take over their lives by over-caring. Because of guilt, they want to do everything for them, as if they are not capable of functioning within that community. This way of caring leads to them over-protecting these people. The process of caring over-shadows people with disability. They simply take over their lives, which results in the fact that these people become object of those who care for them. They are called names and are described by their function or through their disability. This is how they lose their name in life. The above discussion simply explain this object relational syndrome. For example, they are called digole (handicapped). In brief, they lose who they are, when the community uses their characteristic instead of their names, and behaviour becomes a way of dealing with them. The African church finally endorses the above by removing the image and likeness of God from them. For example, when they attend worship, they are viewed as people who are not normal, and in need of prayer, for healing so that they can be normal like us. This is another way of dealing with them as objects. Another obstacle in the African church is lack of ramps. The church is expecting the so-called normal people who function in a way that they want. This is a sign that people with disability are not welcomed. Finally, they are viewed as people possessed by demons and therefore in need of healing. The church, without finding out what they need, sets the agenda. The reader will now understand why the African church has neglected them.